COMPARATIVE EVALUATION OF ANTIMICROBIAL EFFECTS OF SILVER NANOPARTICLES WITH ANTIMICROBIAL PROPERTIES OF COPPER AND ZINC - Vaishnavi, Allour; Sasanka, Keerthi; A.K., Anjali (International Journal of Psychosocial Rehabilitation, 2020)
The era of associate antibiotic resistance may be a cause for increasing concern as microorganisms still develop adaptive countermeasures against current antibiotics at an atrocious rate. In recent years, studies have reported nanoparticles as a promising difference to medical reagents owing to their exhibited activity in many medical specialty applications, as well as drug and cistron delivery, tissue engineering, and imaging. Moreover, nanomaterial analysis has led to reporting a potential relationship between the morphological characteristics of a nanomaterial and therefore the magnitude of its delivered toxicity. However, the conventional synthesis of nanoparticles requires harsh chemicals and costly energy consumption. In our research, we reviewed a total of 45 articles. The sampling data collection was done by search engines such as PubMed, Google Scholar, Cochrane, Elsevier, and various journals of prosthodontics. The published articles were collected from the years 2005-2020. Here, we tend to review the recent advancements in synthesis techniques for silver, copper, and zinc metal nanomaterials with a spotlight on the toxicity exhibited by nanomaterials of multidimensions. The ever-increasing resistance of pathogens towards antibiotics has caused serious health issues in recent years. It's been shown that by combining trendy technologies like technology and material science with the intrinsic antimicrobial activity of the metals, novel applications for these substances may well be known. Per the reports, metal and metal compound nanoparticles represent a gaggle of materials that were investigated in regard to their antimicrobial effects. This review highlights the advantages of choosing every material or metal-based composite for sure applications while conjointly addressing attainable setbacks and also the harmful effects of the nanomaterials on the setting.